2022
DOI: 10.1109/access.2022.3157977
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Multi-Convex Model Predictive Control for Occlusion-Free Target Tracking With Quadrotors

Abstract: This paper proposes a Model Predictive Control (MPC) algorithm for target tracking amongst static and dynamic obstacles. Our main contribution lies in improving the computational tractability and reliability of the underlying non-convex trajectory optimization. The result is an MPC algorithm that runs real-time on laptops and embedded hardware devices such as Jetson TX2. Our approach relies on novel reformulations for the tracking, collision, and occlusion constraints that induce a multi-convex structure in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…Robotont is being continuously validated as an educational tool and a research platform - notable examples of such results have already been reported in a number of research publications [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . More specifically, this robot has been extensively used to deliver university teaching, professional training, and online courses on the topics of ROS and robotics as described in [20] , [21] , [22] , [23] .…”
Section: Validation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotont is being continuously validated as an educational tool and a research platform - notable examples of such results have already been reported in a number of research publications [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . More specifically, this robot has been extensively used to deliver university teaching, professional training, and online courses on the topics of ROS and robotics as described in [20] , [21] , [22] , [23] .…”
Section: Validation and Characterizationmentioning
confidence: 99%
“…[28] , [29] , [30] , [31] , [32] ) and a platform to validate cutting-edge robotics research about e.g. software frameworks [24] and motion-planning [25] , [26] , [27] .…”
Section: Validation and Characterizationmentioning
confidence: 99%
“…From the perspective of the modeling process, there are mainly two modeling methods: Identification modeling and Mechanistic modeling. The former relies on observed input and output data to establish corresponding mathematical models, which lacks a profound understanding of the internal principles and mechanisms of the system [11,12]. In [13], a nonlinear dynamics model for hydraulic construction robot was established base on a novel identification algorithm to realize the trajectory tracking performance.…”
Section: Introductionmentioning
confidence: 99%